First report of Phytopythium vexans causing gummosis and root rot of Khasi Mandarin (Citrus reticulata Blanco) in north eastern states of India - Singh, Dinesh (Plant disease, 2024)
Khasi mandarin (Citrus reticulata Blanco) is the most economically important crop among the citrus growing region in the north-eastern India (Singh et al. 2016). An extensive survey was conducted to identify the causal agent of citrus root rot and gummosis in north eastern states (Meghalaya, Tripura, Manipur, Arunachal Pradesh, Sikkim, Nagaland and Assam) of India during October 2021-23. The gummosis disease incidence ranged from 5 to 95 % in 10 to 25 years old Khasi mandarin plants showing relatively more chronic symptoms on mature trees. Yellowing and dropping of leaves, twigs die back, gum oozing from infected bark and loss of feeder roots were the typical symptoms of the disease. Infected bark tissue and young lemon leaf baits in rhizosphere soil were plated on corn meal agar medium supplemented with pimaricin (10 µg/ml), ampicillin (250 µg/ml), rifamycin (10 µg/ml) and 300µg/ml carbendazim and incubated at 26℃. Fifty isolates were purified and maintained on Carrot agar medium. These isolates showed similar cultural and morphological characteristics. Two representative isolates from Arunachal Pradesh (AP21 and AP26) were selected for further experiments and deposited to Indian Type culture collection (ITCC), New Delhi with accession no. 9156 and 9157 respectively. The colonies were fast growing, showing rosette pattern along with whitish blooming mycelium appearance with no visual sporulation at the surface. The hyphae were coenocytic with initially right-angled branching. Sporangia were globose or sub globose and papillated. Oogonia were smooth and globose (16.29-21.09 µm) in diameter. Antheridia were irregular, cylindrical and broadly attached to oogonia. Empty sporangia were also observed. Multilocus phylogenetic analysis using internal transcribed spacer region (Das et al. 2011), β tubulin (Blair et al. 2008) and Cytochrome oxidase II gene (Noireung et al. 2020) showed that these isolates formed a stable clade with Phytopythium vexans (CBS119.80) sequence retrieved from NCBI database. BLAST analysis showed that ITS sequence of AP21 (OQ372986) and AP26 (OQ381083) had >99 % identity with P. vexans isolate NS-3 (ON533631). Further, BLAST analysis of β tubulin (AP21 OQ446053, AP26 OR405377) and Cox II gene (AP21 OQ473414, AP26 OR552422) sequences showed that our Indian isolates showed >99 % similarity with P. vexans voucher strain CBS119.80. To fulfil Koch's postulates, Khasi mandarin (Citrus reticulata) seedlings were inoculated by adding 100 ml zoospore suspension of P. vexans (1x105 spores/ml) in sterilized soil (Thao et al. 2020). The experiment was carried out in triplicate. Yellowing of leaves and leaf drop were observed 7 days post inoculation while 30 days post inoculation, treated plants started showing symptoms of root rot, including mild root decay. No symptoms were observed in control treatment. The pathogen was reisolated from symptomatic roots and confirmed through colony and sporangium morphology. Recently, it was reported that P. vexans is associated with apple and pear decline in the Saiss plain of Morocco (Jabiri et al. 2021), root rot on mandarin in Thailand (Noireung et al. 2020) and on Durian in Vietnam (Thao et al. 2020). As per our knowledge, this is the first report of P. vexans causing root rot and gummosis in Khasi mandarin from north eastern states of India. This finding is significantly important for the development of a successful disease management strategy in India